On the model of hybrid electronic publishing - E. .. Pavlovskja; M. .. Milanova (Библиосфера)
The model of a hybrid publishing, developed and approved on the basis of the Bulgarian publishing house «e-Book» is presented. The functional characteristics of the model and the tasks of marketing communications for hybrid electronic publishing-house are described.